Relationship Between Girls’ Internet Addiction and Their Mothers’ Psychological and Spiritual Healt - Zahra Ahmadi; Mina Jafarizadeh; Hamid Haghani (Journal of Client-centered Nursing Care, 2018)
Background: Although the internet has prevailed in every aspect of our life, it can be addictive, especially for the adolescents. This study aimed to investigate the relationship between internet addiction in female school students and their mothers’ mental health and spiritual wellbeing. Methods: This is a descriptive correlational study conducted on 400 senior high school female students and their mothers. The study sample was selected using a multi-stage cluster sampling method. Data was collected by a demographic survey form, Persian version of Internet Addiction Test (IAT), General Health Questionnaire (GHQ), and Spiritual Well Being Questionnaire (SWBQ) and was analyzed by descriptive and inferential (ANOVA, t-test, and linear regression analysis) statistics using SPSS-PC V. 20. Results: About 86% of the students were normal internet users. Around 36.8% of the mothers had mild mental health problems, and 94.3% had high spiritual wellbeing. There was a significant negative relationship between internet addiction and spiritual wellbeing and its two dimensions (religious and existential wellbeing) (r=-0.454, P<0.001). The internet addiction had a significant positive relationship with the mothers’ mental health (r=0.341, P<0.001). Conclusion: Studying the problem of internet addiction among female students and paying attention to the mental health and spiritual wellbeing of families, especially mothers, in order to improve their health status seems necessary. Hence, authorities should develop appropriate strategies in this area.